Peningkatan Hasil Belajar IPS Menggunakan Model Pembelajaran Konsep Pada Siswa - Okta Rosfiani; Sinta Bella; Ahmad Miftahfarid; Ahmad Harlan Fahrurozi; Muhammad Rozaktana (Departement of Mathematics Education, 2025)
Social Sciences (IPS) education has an important role in forming students' understanding of society and the surrounding environment. However, many students have difficulty understanding the concepts taught. Therefore, this research aims to improve social studies learning outcomes by implementing a more interactive and interesting concept learning model.This research was conducted in an elementary school in Jakarta involving two different classes. One class uses conventional learning methods, while the other class applies a concept learning model. Learning outcome measurements were carried out before and after implementing this method.The concept learning model used in this research includes teaching strategies that prioritize in-depth understanding through group discussions, use of visual media, and practical activities. Students are invited to actively participate and relate social studies concepts to their daily experiences.The research results show a significant increase in student learning outcomes using the concept learning model compared to conventional methods. The average student final exam score increased by 20%, and the level of student engagement in the learning process also showed positive progress.